2022
DOI: 10.3390/ijerph19074133
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Rehabilitation in Long-COVID-19 Patients with Persistent Breathlessness and Fatigue: The COVID-Rehab Study

Abstract: (1) Background: Cardiopulmonary and brain functions are frequently impaired after COVID-19 infection. Exercise rehabilitation could have a major impact on the healing process of patients affected by long COVID-19. (2) Methods: The COVID-Rehab study will investigate the effectiveness of an eight-week cardiopulmonary rehabilitation program on cardiorespiratory fitness (V˙O2max) in long-COVID-19 individuals. Secondary objectives will include functional capacity, quality of life, perceived stress, sleep quality (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 41 publications
(57 reference statements)
1
23
0
3
Order By: Relevance
“…Myalgia and palpitations were also frequent in the present study which was not in agreement with previous studies [5.9% for myalgia ( 13 ) and 8.3% for palpitations ( 14 )]. Finally, respiratory symptoms, including cough (14%) and breathlessness (28%) were less frequent than expected and in comparison, with other studies ( 15 , 16 ) where respiratory symptoms are more frequent (30–50% for breathlessness).…”
Section: Discussionsupporting
confidence: 62%
“…Myalgia and palpitations were also frequent in the present study which was not in agreement with previous studies [5.9% for myalgia ( 13 ) and 8.3% for palpitations ( 14 )]. Finally, respiratory symptoms, including cough (14%) and breathlessness (28%) were less frequent than expected and in comparison, with other studies ( 15 , 16 ) where respiratory symptoms are more frequent (30–50% for breathlessness).…”
Section: Discussionsupporting
confidence: 62%
“…However, with very mild symptoms, only prolonged and exhaustive activity might be avoided, limiting activity to light efforts [ 110 ]: patients with mild symptoms can exercise, but they should not increase training during the acute phase of the illness [ 111 ]. Once recovered, a progressive increase in exercising is suggested and has been experimenting with various protocols lasting four weeks at least: 12 sessions (three 50-min/1-h sessions per week for four weeks, or two sessions per week for six weeks) [ 112 , 113 ], eight weeks twice a week [ 114 ], three times per week over eight weeks or longer [ 115 ], the activity’s intensity varying from medium to high. Cattadori et al reported that the literature on COVID-19 exercising, by trials or expert consensus, suggests practicing aerobic and resistance training, respiratory, diaphragmatic and cough exercises, and stretching [ 107 ].…”
Section: Exercise Prescription As Medicine For Long Covid-19: Cues An...mentioning
confidence: 99%
“…Cardiorespiratory fitness, muscle function, and joint health should be assessed to detect primary manifestations of long COVID-19 syndrome (such as exertional fatigue and dyspnea), tailor physical exercise, enhance functional capacity and health [ 108 ], and improve quality of life. Several papers reported that, among the functional screening and assessment procedures, the most popular seems to be the 6-Minute Walking Test to estimate the aerobic capacity and exercise tolerance [ 107 , 109 , 114 , 115 , 116 , 118 , 126 ] and the hand grip to measure strength [ 107 , 114 , 116 ]. In addition, laboratory tests such as spirometry and transthoracic echocardiogram are frequently used to evaluate cardiorespiratory functionality with direct measurements [ 107 ].…”
Section: Exercise Prescription As Medicine For Long Covid-19: Cues An...mentioning
confidence: 99%
See 2 more Smart Citations